Low cycle fatigue of hybrid woven kenaf fiber reinforced epoxy composite with 1% addition of silica aerogel - Chok, Ellyna Yee Ling; Abang Abdul Majid, Dayang Laila (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This paper presented the mechanical and fatigue behavior of woven kenaf fiber reinforced epoxy composites with the composition of 16.67% kenaf and 83.33% of epoxy (1:5 weight ratio) with 1% of silica aerogel. Hand lay-up technique was used to prepare the specimens. Fatigue test was conducted at constant stress amplitude, 5 Hz frequency, 0.5 stress ratios and the maximum stress applied was from 90 % to 70 % of ultimate tensile strength (UTS) with decrement of 5%. From the results, tensile properties and fatigue life improved as silica aerogel is added into the composite.